Studi Pelaksanaan Program Djarum Beasiswa Plus - Iqbal, Muhammad (Jurnal Ilmu Kesejahteraan Sosial, 2010)
The research discusses about the Social Capital Formation Among Djarum Scholars/ Beswan Djarum (The Study of Implementation of Djarum Beasiswa Plus Program). In order to explain the matter, the approach that is used is descriptive qualitative research design. The results showed that the formation of social capital is related to the activity which was followed by Beswan Djarum as a process of both formal and informal processes. The Informal and formal process can enhance and broaden interaction among Beswan Djarum and produces a variety of benefits.